Immunoinformatics Design of Multi-Epitope Peptide-Based Vaccine Against Schistosoma mansoni Using Transmembrane Proteins as a Target - Sanches, Rodrigo C. O.; Tiwari, Sandeep; Ferreira, Laís C. G.; Oliveira, Flávio M.; Lopes, Marcelo D.; Passos, Maria J. F.; Maia, Eduardo H. B.; Taranto, Alex G.; Kato, Rodrigo; Azevedo, Vasco A. C.; Lopes, Debora O. (Frontiers in Immunology, 2021)
Schistosomiasis still remains a serious health issue nowadays for an estimated one billion people in 79 countries around the world. There has been great effort made to identify good vaccine candidate during the last decades, but only three molecules reached clinical trials so far. The reverse vaccinology approach has become an attractive option for vaccine design, especially regarding parasites like Schistosoma spp. that presents limitations for culture maintenance. This strategy also has been prompted the construction of multi-epitope based vaccines, with great immunological foreseen properties as well as less prone to contamination, autoimmunity and allergenic responses. Therefore, in this study we applied a robust immunoinformatics approach, targeting S. mansoni transmembrane proteins, in order to construct a chimeric antigen. Initially, the search for all hypothetical transmembrane proteins in GeneDB provided a total of 584 sequences. Using the PSORT II and CCTOP servers we reached 37 plasma membrane proteins, from which extracellular domains were used for epitope prediction. Nineteen common MHC-I and MHC-II binding epitopes, from eight proteins, comprised the final multi-epitope construct, along with suitable adjuvants. The final chimeric multi-epitope vaccine was predicted as prone to induce B-cell and IFN-γ based immunity, as well as presented itself as stable and non-allergenic molecule. Finally, molecular docking and molecular dynamics foreseen stable interactions between the putative antigen and the immune receptor TLR 4. Our results indicate that the multi-epitope vaccine might stimulate humoral and cellular immune responses and could be a potential vaccine candidate against schistosomiasis.